The Effect Of Organizational Culture And Work Environment On Employee Performance With Moderation Of Organizational Citizenship Behavior At Bank Jatim Hr Muhammad Surabaya Branch - Aulia Permata Hati; Lutfi Lutfi (Islamic University of Kalimantan MAB Banjarmasin, 2026)
This study aims to analyze the influence of organizational culture and work environment on employee performance with Organizational Citizenship Behavior (OCB) as a moderating variable at Bank Jatim HR Muhammad Surabaya Branch. This study was motivated by fluctuations in employee performance as reflected in KPI achievements and inconsistencies in previous studies regarding the relationship between variables. A quantitative approach was used with convenient sampling. Data were collected through questionnaires distributed to employees and analyzed using Partial Least Square–Structural Equation Modeling (PLS-SEM). The results of the study indicate that organizational culture and work environment have a positive and significant effect on employee performance. OCB also has a positive effect on performance and is proven to moderate the influence of organizational culture and work environment on employee performance. This means that the higher the level of OCB, the stronger the influence of organizational culture and work environment in improving performance.